2020
DOI: 10.1038/s41598-020-77547-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinformatic design of a COVID-19 subunit vaccine using entire structural immunogenic epitopes of SARS-CoV-2

Abstract: Coronavirus disease 2019 (COVID-19) is an acute pneumonic disease, with no prophylactic or specific therapeutical solution. Effective and rapid countermeasure against the spread of the disease’s associated virus, SARS-CoV-2, requires to incorporate the computational approach. In this study, we employed various immunoinformatics tools to design a multi-epitope vaccine polypeptide with the highest potential for activating the human immune system against SARS-CoV-2. The initial epitope set was extracted from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 76 publications
0
55
0
Order By: Relevance
“…To date, several studies using predictive algorithms to analyze SARS-CoV-2 have been reported ( Alam et al, 2020 ; Behmard et al, 2020 ; Can et al, 2020 ; Chen et al, 2020a ; Dong et al, 2020 ; Poran et al, 2020 ; Saha, Ghosh & Burra, 2021 ; Sohail et al, 2021 ). However, most of these bioinformatics analyses against SARS-CoV-2 intended to develop effective vaccines to prevent infection and the identified sequences possess high homology with other viruses, especially SARS-CoV ( Bhattacharya et al, 2020 ; Chen et al, 2020a ; Robson, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies using predictive algorithms to analyze SARS-CoV-2 have been reported ( Alam et al, 2020 ; Behmard et al, 2020 ; Can et al, 2020 ; Chen et al, 2020a ; Dong et al, 2020 ; Poran et al, 2020 ; Saha, Ghosh & Burra, 2021 ; Sohail et al, 2021 ). However, most of these bioinformatics analyses against SARS-CoV-2 intended to develop effective vaccines to prevent infection and the identified sequences possess high homology with other viruses, especially SARS-CoV ( Bhattacharya et al, 2020 ; Chen et al, 2020a ; Robson, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 30 , 64 , 99 , 103 The ability to design new peptide-based vaccines has received a major boost from the availability of epitope-mapping tools such as the immune epitope database (IEDB) for predicting B- and T-cell epitope sequences ( Table 3 ). 106 , 107 In addition, a number of immunoinformatics approaches have emerged to facilitate the prediction-making process for multiepitope vaccine design, 30 , 64 , 65 , 94 , 100 , 102 , 104 , 108 including computational tools that predict epitope binding to diverse HLA alleles ( e.g ., the IEDB population coverage tool). 107 It is also possible to use HLA ligandome analysis for calculating the probability of peptide interactions with consensus motifs, including 3D predictions for viral peptide docking to cytokine-inducing receptors ( e.g ., TLR2 and TLR4).…”
Section: Nano-enabled Protein Subunit/peptide Vaccines and Virus-likementioning
confidence: 99%
“… 109 Collectively, these tools now enable multiepitope vaccine design to test the feasibility of obtaining cooperative B- and T-cell interactions, as well as possibly soliciting specific CD4 + and CD8 + T-cell responses (discussed in a later section). 30 , 64 , 65 , 102 , 104 , 108 , 110 …”
Section: Nano-enabled Protein Subunit/peptide Vaccines and Virus-likementioning
confidence: 99%
See 1 more Smart Citation
“…These epitopes contains short amino acid sequence that can induce more direct and specific immune response, which overcome the disadvantages of live attenuated vaccines 11 . In-silico based epitope prediction methods have reduced the time consumption and money spent on false epitope candidates and this tools has been employed to develop multiepitope vaccine against several diseases such as Dengue, SARS-CoV-2, Mycobacterium tuberculosis, Steaphylococcus aureus etc [12][13][14][15][16][17] . Hence, the present investigation has adapted this approach for rational design of epitope-based vaccine against KFDV.…”
Section: Introductionmentioning
confidence: 99%